Is there an oncological interest in the combination of CRS/HIPEC for peritoneal carcinomatosis of HCC? Results of a multicenter international study. Issue 11 (November 2018) - Mehta, Sanket; Schwarz, Lilian; Spiliotis, John; Hsieh, Mao-Chih; Akaishi, Eduardo H.; Goere, Diane; Sugarbaker, Paul H.; Baratti, Dario; Quenet, François; Bartlett, David L.; Villeneuve, Laurent; Kepenekian, Vahan; et al.
Abstract: Introduction: Peritoneal metastasis (PM) of hepatocellular carcinoma (HCC) without distant spread are rare. The related prognosis is poor without standard treatment available. The role of cytoreduction surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) is poorly documented. Methods: An international multicentric cohort was constituted by retrospective analysis of 21 patients undergoing CRS/HIPEC for PM of HCC between 1992 and 2016 from 10 reference centers of PSOGI. Data on clinical features, treatment strategies, and survival outcomes were analyzed. Results: The median time interval from the diagnosis of PM to the procedure was 4.5 months. The median peritoneal cancer index was 14. Sixteen patients had complete cytoreduction (CCR0-1). Ten patients had grades 3 to 4 complications. The median duration of follow-up was 52.2 months. The median OS was 46.7 months. The projected 3y-OS and 5y-OS were 88.9 and 49.4% respectively. The median OS for patients with CCR0-1 resection was not reached whereas it was 5.9 months for those with CCR2-3 resection after CRS (p = 0.0005). The median RFS was 26.3 months and projected RFS at 3 years of 36.5 months Three prognostic factors were associated with improved RFS in the univariate analysis: preoperative chemotherapy (p = 0.0156), PCI >15 (p = 0.009), Number of chemotherapy agents used for HIPEC (p = 0.005). Conclusion: CRS/HIPEC is a safe and effective approach in selected patients with PM of HCC. CRS/HIPEC gives the patient a chance for a good relapse free and overall survival and should be considered as an option.